Quantitative Trait Locus Mapping and Identification of Candidate Genes for Resistance to Fusarium Wilt Race 7 Using a Resequencing-Based High Density Genetic Bin Map in a Recombinant Inbred Line Population of Gossypium barbadense - Han, Wanli; Zhao, Jieyin; Deng, Xiaojuan; Gu, Aixing; Li, Duolu; Wang, Yuxiang; Lu, Xiaoshuang; Zu, Qianli; Chen, Qin; Chen, Quanjia; Zhang, Jinfa; Qu, Yanying (Frontiers in Plant Science, 2022)
Fusarium wilt caused by Fusarium oxysporum f. sp. vasinfectum (FOV) is one of the most destructive diseases in cotton (Gossypium spp.) production, and use of resistant cultivars is the most cost-effective method managing the disease. To understand the genetic basis of cotton resistance to FOV race 7 (FOV7), this study evaluated a recombinant inbred line (RIL) population of 110 lines of G. barbadense from a cross between susceptible Xinhai 14 and resistant 06-146 in eight tests and constructed a high-density genetic linkage map with resequencing-based 933,845 single-nucleotide polymorphism (SNP) markers covering a total genetic distance of 2483.17 cM. Nine quantitative trait loci (QTLs) for FOV7 resistance were identified, including qFOV7-D03-1 on chromosome D03 in two tests. Through a comparative analysis of gene expression and DNA sequence for predicted genes within the QTL region between the two parents and selected lines inoculated with FOV7, GB_D03G0217 encoding for a calmodulin (CaM)-like (CML) protein was identified as a candidate gene. A further analysis confirmed that the expression of GB_D03G0217 was suppressed, leading to increased disease severity in plants of the resistant parent with virus induced gene silencing (VIGS).